Voltage regulation in distribution networks by electrical vehicles with online parameter estimation - Lyu, Shukang; Han, Huachun; Li, Jingyan; Yuan, Xiaodong; Wang, Wenyue (Frontiers in Energy Research, 2024)
The integration of a large number of electric vehicles (EVs) offers a new perspective for providing voltage regulation services for the operation of distribution networks. In this paper, we utilize EV clusters by controlling the discharging power to realize voltage regulation of distribution networks. We formulate a feedback-based optimization problem with the objectives of minimizing voltage mismatch as well as reducing the cost of voltage regulation services provided by EV clusters. Then we propose an algorithm with online resistance estimation to find the optimal solution without requiring complete information about distribution networks. The convergence of the proposed algorithm is guaranteed by theoretical proof. Numerical results in 33-bus system validate the performance of the algorithm.